(untitled) (Fiep Bulletin - online, 2014)
This study aimed to evaluate the similarities and differences between the Multieducacao basic curriculum core and the reality of Physical Education teachers from the network of municipal education of Rio de Janeiro. Through a field study with application of a mixed questionnaire to 29 teachers we noticed that 83% of teachers say knowing such a document. Of the 12 Multieducação proposals submitted by this study for analysis, it was found that five of them are different from the practice teaching, while other five are converging with the practice teaching, which makes us conclude that in fact there are similarities and differences between the themes proposed in Multieducação and its applicability on the part of teachers in their schools.